AGAMA SEBAGAI ALIENASI Analisis Kritis Atas Pemikiran Karl Marx dalam Perspektif Studi Agama - Nurmiati, Ai Siti; Hammami, Chaima; Truna, Doddy S.; Rosyad, Rifki (PT. Hafasy Dwi Nawasena, 2026)
This article discusses the concept of religion as a form of alienation in Karl Marx’s thought and its relevance to contemporary religious studies. For Marx, religion is not merely a spiritual system but a social phenomenon reflecting economic and political conditions. Religion functions as the “opium of the people,” an ideological instrument that pacifies human suffering under social injustice. This study examines Marx’s theory of alienation and compares it with the ideas of Ludwig Feuerbach, Émile Durkheim, and Max Weber. The analysis shows that although Marx’s theory appears reductionist for viewing religion only through material conditions, it remains vital in understanding the relationship between faith, ideology, and social structures in religious studies.